Training of development recycle-based mathematics learning media for visual impairment students - Sumbaji Putranto; Gading Julio Perkasa; Cut Intan Maulidia; Diah Putri Sulistyowati; Fatikha Zulfatul Aulia; Dwi Lestari Endang Pratitis; Afiah Nurrizky (Universitas Muhammadiyah Magelang, 2024)
Visually impaired (VI) students in inclusive classrooms often struggle with understanding mathematical concepts. A limited availability of suitable and user-friendly learning materials exacerbates this challenge. This community service program aimed to enhance the capacity of junior high school mathematics teachers in Sleman Regency to develop effective, recycled-material-based learning media for VI students. A two-day training was conducted for 36 mathematics teachers, encompassing lectures, discussions, and media development workshops. Training outcomes demonstrated a significant improvement in teacher understanding, as evidenced by the post-test average rising from 54.7 to 77.2. Moreover, teachers successfully created 18 innovative learning media for immediate classroom application.